The Coverage Of Islam/muslims And Terrorism In International Media - Sofia Hayati Yusoff; Rosninawati Hussin; Siti Nubailah Mohd Yusof (Global Academy of Training and Research, 2024)
Objective - In portraying Islam, especially after the September 11 attacks, a number of studies found that terrorism has been repeatedly associated with Islam/Muslims by most of the international media. There is a perception that international media play a vital role in creating a relationship between Islam/Muslims and terrorism in their coverage that leads to the formation of frames on Islam/Muslims and terrorism. Methodology/Technique - Based on this view, the researcher has conducted a content analysis of two international news magazines, Time and The Economist, aimed at examining the frames at four different periods of sampling; a one year period right before September 11, a one year period right after September 11, a one year period after five years of September 11 and a one year period after ten years of September 11. This study has applied a content analysis as the research methodology in collecting, coding and analyzing the data. All paragraphs pertaining to the issue during the study periods were analyzed. A total of 4,443 paragraphs was analyzed to determine the existence of frames. Findings - The researcher has found the total of ten significant frames used by both Time and The Economist in covering stories related to Islam/Muslims throughout the four periods being studied. Novelty – This study expands the research made before on the labeling of international media on Islam and terrorism in terms of the time frame, scopes of indicators and measurement as well as the types of media selected.